Teknik Bermain Kertas untuk Meningkatkan Prestasi Belajar Matematika tentang Bilangan Pecahan pada Siswa Kelas IV Sekolah Dasar - Siswanto, Siswanto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The identification results that have been obtained show that there are several problems in the learning process. The things that cause problems are that teachers have not used appropriate learning techniques/strategies, teacher explanations are less interesting so students feel bored, learning is still dominated by teachers, teachers have not used the right learning media, teachers are lacking in providing motivation to students. . From the results of the problem analysis above, the researcher created Classroom Action Research which aims to improve the quality of learning. After the researchers carried out a series of classroom action research activities, the following results were obtained: the paper playing technique can improve the learning achievement of class IV students at SD Negeri 2 Nanggulan in mathematics lesson material about fractions. This can be seen from the following description: before the revision, 33.33% of students had completed the KKM and 66.67% of students had not completed the KKM; implementation of cycle I, 58.33% of students completed the KKM and 31.67% of students had not completed the KKM, implementation of the cycle, 91.67% of students had completed the KKM and 8.33% of students had not completed the KKM. With paper playing techniques, students' interest and enthusiasm for learning mathematics increases. Paper playing techniques can also increase students' learning motivation.